2005
DOI: 10.1111/j.1600-0501.2005.01097.x
|View full text |Cite
|
Sign up to set email alerts
|

The sinus lift with phycogenic bone substitute

Abstract: Sinus lift carried out with phycogenic bone substitute was shown to be an effective method with limited invasiveness and a high survival rate of implants (97.8%).

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
31
0
2

Year Published

2007
2007
2014
2014

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 25 publications
(33 citation statements)
references
References 18 publications
(25 reference statements)
0
31
0
2
Order By: Relevance
“…Biopsy specimens were harvested and dental implants were placed after a 9-month healing period in the present study. This healing period was chosen because it was the time point used in previously reported maxillary sinus and alveolar augmentation studies [33]. Cellular differentiation, augmentation material breakdown, and bony replacement were noted to be evident at the grafted sites largely preserving the dimensions of the alveolar ridge after 9 months of healing [33].…”
Section: Discussionmentioning
confidence: 99%
“…Biopsy specimens were harvested and dental implants were placed after a 9-month healing period in the present study. This healing period was chosen because it was the time point used in previously reported maxillary sinus and alveolar augmentation studies [33]. Cellular differentiation, augmentation material breakdown, and bony replacement were noted to be evident at the grafted sites largely preserving the dimensions of the alveolar ridge after 9 months of healing [33].…”
Section: Discussionmentioning
confidence: 99%
“…[17] In this study, we observed that after 6 months 43% of Algipore is still present, once again in line with the results obtained by Schopper after 7 months (33% ± 7.8%) and by Scarano et al after 6 months (37.1% ± 3.8%). [17] We know, from the previous study of Simunek et al [33] that Algipore is gradually resorbed and replaced by newly formed bone. During the time period of 6-15 months, the percentage of newly formed bone grows linearly, and the percentage of Algipore decreases linearly.…”
Section: S E V E R a L S T U D I E S R E P O R T E D T H E U S I N G mentioning
confidence: 99%
“…Porous biomaterials, such as Algipore, act as a scaffold for tissue regeneration. [15,17,33,35] They guide cell and vessels migration into the pores. Cell and vessel movement inside the pores are related to the degree of interconnection of the pores and to its size.…”
Section: S E V E R a L S T U D I E S R E P O R T E D T H E U S I N G mentioning
confidence: 99%
See 2 more Smart Citations